Postoperative Alcaligenes xylosoxidans endophthalmitis: Report of two cases (2008)
We report two cases of postoperative Alcaligenes xylosoxidans endophthalmitis. A 78-year-old woman in good general health developed A. xylosoxidans endophthalmitis one month after an uncomplicated phacoemulsification procedure with posterior chamber intraocular lens. It was performed on her left eye, at another institution. Removal of the intraocular lens and capsule was performed because of recurrent inflammation after vitrectomy and intravitreal antibiotic injections. Her son, a 55-year-old man, developed A. xylosoxidans endophthalmitis in his left eye, two months after an uncomplicated phacoemulsification procedure with posterior chamber intraocular lens (it also was performed by the same surgeon). He also required vitrectomy with removal of the intraocular lens and capsule because of persistent disease. A. xyloso - xidans can cause chronic low-grade and progressive endophthalmitis after cataract extraction that is often resistant to corrective antibiotic therapy. This kind of case is rare. There have been only previously reported seven cases worldwide to the best of our knowledge.